Bioactive compounds from mushrooms: Emerging bioresources of food and nutraceuticals. (December 2022) - Kour, Harpreet; Kour, Divjot; Kour, Satvinder; Singh, Shaveta; Jawad Hashmi, Syed Azhar; Yadav, Ajar Nath; Kumar, Krishan; Sharma, Yash Pal; Ahluwalia, Amrik Singh
Abstract: Mushrooms have been an indispensable element of the human culture since antiquity and are cherished all over the globe for their nutritive and therapeutic benefits. Being acknowledged as "the new superfood" of the future, they are a cardinal component of human diet for boosting health status and well being. Mushrooms are endowed with antioxidant, antimicrobial, anticancer, prebiotic, antidiabetic, and anti-inflammatory activities, upholding a great therapeutic potential and a huge spectrum of clinical applications. The wide ranges of bioactive compounds including polysaccharides, polysaccharides protein complexes, peptides and proteins, terpenoids and phenolic compounds have been reported from diverse groups of mushroom. Laden with a wealth of nutrients and innumerable biomolecules of therapeutic worth, they are internationally appreciated and envisaged as world's largest untapped resources of dietary supplements. In the recent years, owing to significant healthier lifestyle changes, dietary practices of people and consumers opting for immunity enhancing supplements especially during the COVID-19 pandemic, the yearning for mushroom based nutraceuticals and functional foods is on rise. This review gives comprehensive details on the biodiversity of mushrooms, its nutritional and medicinal importance, secondary metabolites especially of nutraceuticals and pharmaceutical potential, and their role as bioactive agents and application in preparing mushroom based value-added products.